초장거리 LoRa 통신 모듈 설계 및 구현 - 김동현(Dong-Hyun Kim); 허준환(Jun-Hwan Huh); 이창홍(Chang-Hong Lee); 김광덕(Kwang-Deok Kim); 김종덕(Jong-Deok Kim) (한국정보통신학회논문지, 2022)
Internet of Things(IoT) is a communication technology that collects information of object remotely and controls the function of object by adding a communication function to object that does not have a communication function. For the IoT, various communication technologies such as Wi-Fi, 3GPP, and Bluetooth are available, and Long Range(LoRa) is communication technologies specialized in the IoT concept. LoRa is a communication technology that support long-distance, low-power, and low-speed communication, and is suitable for collecting information generated form object in remote equipment and controlling equipment. Because of these characteristics, it is used in many application field, and various performance improvement studies are in progress. This paper intends to propose an ultra-long-range LoRa communication module that can be used in a wider range of applications. We design and implement hardware, firmware, and application software for testing to develop ultra-long-range LoRa communication modules. The implemented module will be tested in a real environment to verify its performance and to check its utilization. 사물인터넷은 통신 기능이 없는 사물에 통신 기능을 추가하여 사물의 정보를 원격에서 수집 및 사물의 기능을 제어하는 통신기술이다. 이를 위해 Wi-Fi, 3GPP, 블루투스 등 다양한 통신기술이 사용 가능하며 NB-IoT와 LoRa(Long Range)는 사물인터넷 개념에 특화된 통신기술이다. LoRa는 장거리, 저전력, 저속 통신을 지원하는 통신기술로 원거리의 사물에서 생성되는 정보를 수집하고 장비를 제어하기에 적합하다. 이러한 특징 때문에 많은 응용 분야에서 활용되고 있으며 다양한 성능 향상 연구가 진행 중이다. 본 논문은 더욱더 넓은 응용 분야에서 활용하기 위한 초장거리 LoRa 통신 모듈을 제안하고자 한다. 초장거리 LoRa 통신 모듈을 개발하기 위해 하드웨어, 펌웨어 및 테스트를 위한 응용 소프트웨어를 설계 및 구현한다. 구현된 장비는 실제 환경에서 테스트를 통해 성능을 검증하여 활용도를 확인하겠다.